(untitled) (Journal of the Bangladesh Agricultural University, 2010)
The Phenotypic characteristics of three genotypes of native chicken comprising of Non-descript Desi (ND), Hilly (H) and Naked Neck (NN) were studied. A total of 180 individual chickens (Male: ND= 20; H= 20 and NN=20; Female: ND= 40, H=40 and NN = 40) were characterized under intensive management system for qualitative and quantitative traits. The results indicated that the predominant plumage color of three types of native chickens was black brownish (33.33%) followed by white with black tips (28.33 %) and red brownish (18.33%). Values indicate that 35% of native chickens had whitish shank color followed by yellowish 31.68%; black 11.66 % and others 21.67 %. All hens of ND, H and NN laid light brown (62.42%) to cream or off white (30.28%) colored eggs. Variations were also found on quantitative traits such as shank length, body weight and reproductive traits on intensive management system. number of eggs/ hen from starting to ten months of laying were 108, 104 and 112, respectively in ND, H and NN genotypes. Three native chicken genotypes showed distinct physical variations for both qualitative and quantitative traits under intensive management system. Keywords: Native chicken; Quantitative traits; Qualitative traits DOI: 10.3329/jbau.v8i1.6402 J. Bangladesh Agril. Univ. 8(1): 79-82, 2010